2021
DOI: 10.1515/jbcpp-2021-0282
|View full text |Cite
|
Sign up to set email alerts
|

Alpha2-antiplasmin deficiency affects depression and anxiety-like behavior and apoptosis induced by stress in mice

Abstract: Objectives Depression is a psychiatric disorder that affects about 10% of the world’s population and is accompanied by anxiety. Depression and anxiety are often caused by various stresses. However, the etiology of depression and anxiety remains unknown. It has been reported that alpha2-antiplasmin (α2AP) not only inhibits plasmin but also has various functions such as cytokine production and cell growth. This study aimed to determine the roles of α2AP on the stress-induced depression and anxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Additionally, α2AP attenuates Wnt-3a-induced β-catenin expression and mediates Wnt/β-catenin signaling [ 137 ]. Moreover, α2AP is associated with apoptosis [ 152 ], suggesting that α2AP may affect osteocyte apoptosis through the regulation of multiple signaling pathways. Thus, α2AP may mediate bone remodeling and inflammatory bone loss through multiple mechanisms, including plasmin inhibition, pro-inflammatory cytokine production, and the regulation of several signaling pathways.…”
Section: The Role Of Fibrinolytic Factors In Bone Homeostasis and Inf...mentioning
confidence: 99%
“…Additionally, α2AP attenuates Wnt-3a-induced β-catenin expression and mediates Wnt/β-catenin signaling [ 137 ]. Moreover, α2AP is associated with apoptosis [ 152 ], suggesting that α2AP may affect osteocyte apoptosis through the regulation of multiple signaling pathways. Thus, α2AP may mediate bone remodeling and inflammatory bone loss through multiple mechanisms, including plasmin inhibition, pro-inflammatory cytokine production, and the regulation of several signaling pathways.…”
Section: The Role Of Fibrinolytic Factors In Bone Homeostasis and Inf...mentioning
confidence: 99%
“…In addition, profibrotic factors including CTGF, HMGB1 and IFN-γ induce α2AP production in fibroblasts [ 11 , 38 , 66 ], and the increase in α2AP expression may affect fibrosis progression in SSc. Furthermore, it has been reported that α2AP deficiency attenuates oxidative stress [ 117 ] and promotes apoptosis [ 17 ], and α2AP may affect the induction of oxidative stress and resistance to apoptosis in SSc. On the other hand, plasmin can activate MMPs, such as MMP-1, MMP-3, and MMP-9, and degrade ECM [ 118 , 119 , 120 ].…”
Section: α2ap and Fibrosis In Sscmentioning
confidence: 99%
“…α2AP is a serine protease inhibitor (serpin) that rapidly inactivates plasmin on the fibrin clots or in the circulation [ 2 , 8 , 9 ]. α2AP has various biological functions independent of plasmin and is associated with thrombosis, angiogenesis, vascular remodeling, fibrosis, brain functions, and bone homeostasis [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. The expression of α2AP is elevated in SSc dermal fibroblasts, and the blockade of α2AP suppresses the progression of pathology in SSc dermal fibroblasts and SSc model mice [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%